2016
DOI: 10.1016/j.jmb.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine Modification in a Long Noncoding RNA Hairpin Predisposes Its Conformation to Protein Binding

Abstract: N6-methyladenosine (m6A) is a reversible and abundant internal modification of messenger RNA (mRNA) and long noncoding RNA (lncRNA) with roles in RNA processing, transport, and stability. Although m6A does not preclude Watson-Crick base pairing, the N6-methyl group alters the stability of RNA secondary structure. Since changes in RNA structure can affect diverse cellular processes, the influence of m6A on mRNA and lncRNA structure has the potential to be an important mechanism for m6A function in the cell. Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
173
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 39 publications
1
173
0
1
Order By: Relevance
“…In the context of tRNA and rRNA, studies have mostly focused on the impact of Ψ on RNA structure, where it is thought to contribute to structural stability through the potential formation of an extra hydrogen bond Davis 1997, 1999;Kierzek et al 2014). Such a structural role, if present on mRNA, could modulate the ability of RNA binding proteins to bind to the mRNA, perhaps in an analogous manner to the role recently reported for N 6 -methyladenosine Zhou et al 2015) and, in this manner, impact its localization, stability, or translation. In yeast, we previously observed that steady state levels of mRNAs pseudouridylated via Pus7 were ∼25% decreased following knockout of PUS7, suggestive of a potential role for pseudouridine in stabilizing messages (Schwartz et al 2014).…”
Section: Function Of Trub1-mediated Pseuoduridylation Of Mrnamentioning
confidence: 95%
“…In the context of tRNA and rRNA, studies have mostly focused on the impact of Ψ on RNA structure, where it is thought to contribute to structural stability through the potential formation of an extra hydrogen bond Davis 1997, 1999;Kierzek et al 2014). Such a structural role, if present on mRNA, could modulate the ability of RNA binding proteins to bind to the mRNA, perhaps in an analogous manner to the role recently reported for N 6 -methyladenosine Zhou et al 2015) and, in this manner, impact its localization, stability, or translation. In yeast, we previously observed that steady state levels of mRNAs pseudouridylated via Pus7 were ∼25% decreased following knockout of PUS7, suggestive of a potential role for pseudouridine in stabilizing messages (Schwartz et al 2014).…”
Section: Function Of Trub1-mediated Pseuoduridylation Of Mrnamentioning
confidence: 95%
“…Additional protein binding partners of SRA1 were recently reviewed (Liu, et al 2016). SRA1 interacts with DICER (Redfern, et al 2013).…”
Section: Mitochondrial-encoded Lncrnas and Lncrna Imported Into Mitocmentioning
confidence: 99%
“…SRA1 interacts with DICER (Redfern, et al 2013). By its interaction with SLIRP (SRA stem-loop interacting RNA binding protein), SRA1 has a repressive function by recruiting corepressors (reviewed in (Liu et al 2016)). SLIRP represses NR transactivation in an SRA1-dependent manner (Hatchell, et al 2006).…”
Section: Mitochondrial-encoded Lncrnas and Lncrna Imported Into Mitocmentioning
confidence: 99%
“…For most mRNAs, m 6 A modification is most frequently observed in long exons, near stop codons, and in 3′ UTRs (Dominissini et al, 2012; Meyer et al, 2012). Addition of m 6 A can alter mRNA stability, induce RNA conformational changes, modulate protein-RNA interactions, and even modify microRNA processing (Alarcón et al, 2015; Liu et al, 2015b; Wang et al, 2014a; Wang et al, 2015; Zhou et al, 2016). Several studies investigating the sequence specificity of m 6 A modification discovered RRACH (R represents A or G, and H represents A, C or U) as the consensus sequence, with the central A as the methyl acceptor (Csepany et al, 1990; Dominissini et al, 2012; Harper et al, 1990; Meyer et al, 2012; Rottman et al, 1994; Schibler et al, 1977).…”
Section: Introductionmentioning
confidence: 99%